2020
DOI: 10.1177/1758835920947976
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin potentiates celecoxib-induced growth inhibition and apoptosis in human non-small cell lung cancer by targeting GRP78 activity

Abstract: Background: Aspirin has recently emerged as an anticancer drug, but its therapeutic effect on lung cancer has been rarely reported, and the mechanism of action is still unclear. Long-term use of celecoxib in large doses causes serious side effects, and it is necessary to explore better ways to achieve curative effects. In this study, we evaluated the synergistic anticancer effects of celecoxib and aspirin in non-small cell lung cancer (NSCLC) cells. Methods: In vitro, we evaluated the combined effects of celec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Hence, the ATPase catalytic activity was necessary for the anti-apoptotic function of GRP78 through preventing caspase activation 42 . For example, some compounds, such as EGCG, honokiol and aspirin, increase the chemotoxic sensibility toward cancer cells by directly binding to GRP78-NBD to inhibit the ATPase activity 43 , 44 , 45 . Excitedly, in our current study, the subsequent anti-tumor activity assay demonstrated that in CRC LS174-T cells, overexpressed GRP78-N500 truncation (including NBD and membrane translocation sequences) could significantly increase the chemotoxic sensitivity of FMBP to LS174-T cells, accompanied by the elevation of ROS production and the apoptosis rate, as well as the reduction of cell viability radio ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the ATPase catalytic activity was necessary for the anti-apoptotic function of GRP78 through preventing caspase activation 42 . For example, some compounds, such as EGCG, honokiol and aspirin, increase the chemotoxic sensibility toward cancer cells by directly binding to GRP78-NBD to inhibit the ATPase activity 43 , 44 , 45 . Excitedly, in our current study, the subsequent anti-tumor activity assay demonstrated that in CRC LS174-T cells, overexpressed GRP78-N500 truncation (including NBD and membrane translocation sequences) could significantly increase the chemotoxic sensitivity of FMBP to LS174-T cells, accompanied by the elevation of ROS production and the apoptosis rate, as well as the reduction of cell viability radio ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reinterpretation of drug efficacy will avoid the high clinical failure rate caused by ADMET, which reduces the R&D cost and shortens the time of manufacture. Celecoxib was initially approved by the Food and Drug Administration (FDA) as an analgesic, anti-inflammatory and antipyretic drug, followed by a large amount of preclinical evidence showing that celecoxib has a strong killing effect on cancer ( Li et al, 2018 ; Zuo et al, 2018 ; Liu et al, 2019 ; Zhang et al, 2020 ). Therefore, the anticancer activity of maprotiline will be promising for development as a new kind of HCC treatment drug.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GRP78 is considered to be the principal ER stress biomarker. CHOP is an ER-stress-induced apoptosis marker; PERK and IRE1α are ER stress sensor proteins [12][13][14][15][16]. Whether the ER stress trigger is related to the downregulation of TPD52L2 expression in OXA-resistant gastric cells remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%